Advanced protocol to functionalize CaP bioceramic surface with peptide sequences and effect on murine pre-osteoblast cells proliferation. Issue 9 (1st May 2019) - Poli, Evelyne; Magnaudeix, Amandine; Damia, Chantal; Lalloué, Fabrice; Chaleix, Vincent; Champion, Eric; Sol, Vincent
Graphical abstract: Abstract: To bring osteoinductive properties to calcium phosphate (CaP) bioceramics, a silicon-substituted hydroxyapatite was functionalized by integrin-adhesive cyclic-pentapeptides (c-(DfKRG)). A new two-step protocol was set up to immobilize peptides at low and controlled density on the ceramic surface and limit contamination by adsorbed molecules. To this aim, a spacer bearing c-(DfKRG)-S-PEG6 -NHS molecule was synthesized and bonded to an organosilane previously covalently bonded to the ceramic surface. The functionalized ceramic was tested in vitro for MC3T3-E1 murine pre-osteoblasts. CaP ceramic surface retained good biological properties thanks to low density of bonded molecules preserving part of the bioactive CaP surface free of bioorganic molecules. The final SiHA-T-PEG6-S-c-(DfKRG) was shown to increase cell density and to improve proliferation. Furthermore, the use of a strong and stable covalent bond between inorganic and organic parts prevented early burst release of the peptide and increased the persistence of its bioactivity over time. So, this CaP ceramic associating c-(DfKRG) by covalent grafting could be considered as promising new biomaterials for bone tissue engineering.